2016
DOI: 10.1093/scan/nsw121
|View full text |Cite
|
Sign up to set email alerts
|

The role of language in the experience and perception of emotion: a neuroimaging meta-analysis

Abstract: Recent behavioral and neuroimaging studies demonstrate that labeling one’s emotional experiences and perceptions alters those states. Here, we used a comprehensive meta-analysis of the neuroimaging literature to systematically explore whether the presence of emotion words in experimental tasks has an impact on the neural representation of emotional experiences and perceptions across studies. Using a database of 386 studies, we assessed brain activity when emotion words (e.g. ‘anger’, ‘disgust’) and more genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
82
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 77 publications
(125 reference statements)
10
82
0
5
Order By: Relevance
“…For instance, neuroimaging studies show that labeling one’s affect states in a discrete and specific way is associated with down-regulation of the amygdala, a brain region associated with representing negative affect (Brooks et al, 2017; Hariri et al, 2000; Lieberman et al, 2007). Another study found lower activation of the dorsal anterior cingulate cortex and anterior insula, two regions involved in representing negative affect, among individuals with greater emotion differentiation (Kashdan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, neuroimaging studies show that labeling one’s affect states in a discrete and specific way is associated with down-regulation of the amygdala, a brain region associated with representing negative affect (Brooks et al, 2017; Hariri et al, 2000; Lieberman et al, 2007). Another study found lower activation of the dorsal anterior cingulate cortex and anterior insula, two regions involved in representing negative affect, among individuals with greater emotion differentiation (Kashdan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of interest in this task was the difference in brain connectivity when adolescents labeled facial expressions of negative emotions compared to passively viewing them. This task measures implicit emotion regulation thought to be engaged as a result of labeling emotions (Brooks et al, 2016;Gyurak, Gross, & Etkin, 2011;Lieberman et al, 2007). We hypothesized that (a) NE would predict a less mature pattern of amygdala-PFC connectivity; (b) CC would predict a more mature pattern of amygdala-PFC connectivity; and (c) the association between NE and less mature patterns of amygdala-PFC connectivity would be strongest at low levels of CC (i.e., NE x CC interaction), highlighting the independent and interactive effects of childhood traits on emotion regulation in adolescence.…”
Section: Study Overviewmentioning
confidence: 99%
“…Despite the novel contributions of this study, it has noteworthy limitations. First, although previous research suggests emotion labeling is an effective implicit emotion regulation strategy (Brooks et al, 2016;Gyurak et al, 2011;Lieberman et al, 2007), we did not explicitly instruct participants to regulate their emotions during the task. As we cannot be certain that labeling emotions engaged emotion regulation strategies to a similar extent in all of our participants, future studies examining patterns of functional connectivity during explicit emotion regulation tasks are warranted.…”
Section: Contributions and Limitationsmentioning
confidence: 99%
“…To account for the occurrence of specific emotions, a related line of inquiry has documented how other, more context-directed affective dimensions such as dominance, certainty, agency, effort, and attention differentiate reports of emo-tional experiences of similar valence and arousal, such as anger and fear, or hope and pride (1,14,19,(22)(23)(24). Varying combinations of such dimensions have been the focus of hundreds of studies linking reported emotional experience to behavior, physiology, and brain activity (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36).A second approach to emotional experience details how specific emotion categories, such as awe, fear, and envy, describe discrete clusters of states within a presupposed semantic space. More precisely, basic emotion theories posit that a limited number of clusters, ranging in theoretical accounts from 6 to 15, describe the distribution of all emotional states (16,37,38).…”
mentioning
confidence: 99%